Cost-analysis of health impacts associated with emissions from combined cycle power plant. (15th December 2016) - AlRafea, Kamal; Elkamel, Ali; Abdul-Wahab, Sabah A.
Abstract: The economic assessment of expected air pollution levels and its associated health impact requires different investigational stages, including an analysis of specific air pollutants and their emission rates, calculations of air shed concentrations, measurements of exposure, correlations with human health risk responses to air pollutants' exposure changes, and a monetization of human health risks. The study aims to assess the monetary value of pollutant concentrations and the expected risks of those pollutants on human mortality and morbidity as path of a cost analysis. The pollutants carbon monoxide (CO), nitrogen dioxide (NO2 ), fine particles (PM2.5 ), and sulfur dioxide (SO2 ) from a sample natural gas fueled combined cycle power plant were chosen based on their emission rates and their severity on the health impacts with which they are associated. The SCREEN3 dispersion model was used to obtain pollutant concentration estimates, and an air pollutant health impact matrix was established based on health data pooled throughout the study period. To lessen the health impact from natural gas fuel, hydrogen-enriched natural gas (HENG) was used to fuel the combined cycle power plant. The desired hydrogen was collected from renewable energy sources through the electrolysis process in an energy hub system. The Health Canada's Air Quality Benefits Assessment Tool was used for monetizing the impacts of pollutants on health by taking into account a range of morbidity and mortality outcomes as well as their dollar value, when the natural gas and the hydrogen enriched natural gas fuels were used. The total hidden costs of health impacts associated with producing electricity averaged CAD$33.50 per megawatt hour based on the selected area and year in which the scenario was run. It was found that fuelling combined cycle power plant with hydrogen-enriched natural gas up to 5% hydrogen concentrations could save CAD$1.15 per megawatt hour in terms of health impact costs. The health impact cost of PM2.5 had the highest value followed by NO2, SO2, and CO. Graphical abstract: Highlights: Monetizing the Health Impacts due to the exposure of CCPP's air pollutants using AQBAT. Health impacts of NG-fueled CCPP is monetized and compared to HENG-fueled ones. Utilizing HENG fuel could save $1.15/MWh from Health Impacts perspective. A 2.3% of H2 in HENG fuel is a critical value for both LCOE and health impacts. Blending renewable-electrolysis H2 with NG is not yet the best economical solution.